THE IMPACT OF THE APPLICATION OF WOOD ON THE TECHNOLOGICAL PREPARATION FOR FURNITURE MANUFACTURING - Namicev, Petar; Petrovski, Mihail (Journal of process management and new technologies, 2019)
This paper analyzes the influence of the application of wood on the technological preparation of furniture production. When it comes to furniture production the wood as a choice of material is the most used material today as it was in the past. It describes the physical and chemical properties of the wood, its technology for making furniture, as well as the influence of the choice of the type of wood on the application of furniture production. From the conducted research in furniture manufacturing companies it can be concluded that at the moment the most common wood for furniture production in North Macedonia is the beech, the second is the oak, and the third is the walnut. The technologies used to process these types of wood are up to date with world-class technology, and when economies are required, sometimes chipboard and mediapan are also used. The best type of wood for making furniture is the oak, but from the research it can be concluded that besides being less available from the beech, it is also more difficult for processing and requires different machining.